The Effect of EMF Radiation Emitted by Mobile Phone to Insect Population using Drosophila melanogaster as a Model Organism - Fauzi, Ahmad; Corebina, Aloysius Duran (Proceeding International Conference on Global Resource Conservation, 2015)
Electromagnetic field (EMF) exposure has been reported produce a number of biological effects on biomolecules, cells, and up to the entire body of the organisms. Mobile phone devices, the most powerful EMF transmitters in the environment of human life, have become widely and increasingly used by the public. The exponential growth of mobile communications has been accompanied by a parallel increase in the density of EMF. Insects is one component of ecosystems that have various roles, both positive and negative, such as biological control and pests. In this study, the effect of EMF radiation emitted by mobile phone on insect over several generations were observed. Drosophila melanogaster was used as model organism and generation time, adult filial number, and sex ratio were observed in this study. As a result, a cell phone exposure significantly affected the generation time, whereas no significant effect on the adult filial number and sex ratios of D. melanogaster.Â Keywords: Adult filial number; Drosophila melanogaster; EMF; generation time; mobile phone; sex ratio